ENHANCING SELF DEVELOPMENT AND ASSERTIVE BEHAVIOR OF ADOLESCENTS THERAPEUTIC GROUP THERAPY - Fajriyah Nur Afriyanti (Psychiatry Nursing Journal (Jurnal Keperawatan Jiwa), 2024)
Background: Adolescents in fulfilling their growth and development tasks, impact their biology, cognitive, emotional, psychosexual, language, psychosocial and behaviour entering adulthood. The problem adolescents often encounter, in the form of behaviour resulting from this transition period, is how to behave assertively. Therapeutic group therapy allows adolescents to optimally fulfil their growth and development tasks and change their behaviour to be more adaptive. Method: This study used a quasi-experimental design with a sample of 76 adolescents (38 intervention and 38 control). The instruments used were assertive behaviour, behaviour observation sheets, and therapeutic group therapy modules. The intervention group received 7 therapeutic group therapy sessions, each 30-45 minutes. The Assertiveness Inventory by Alberti and Emmons was used to measure adolescent assertive behaviour. Meanwhile, this study used a dependent t-test for data analysis. Results: Respondent characteristics included adolescents aged 13-15 years, females (52.63%), parents' educational level of Bachelor (63.16%), and parents' occupation as employees (42.11). The results show that aspects of adolescent self-development have a mean value of emotional (0.588), cognitive (0.533), language (0.435), and psychosocial (0.378). This indicates that there is a significant and meaningful influence on adolescents' assertive behaviour before and after TGT (α=0.05 and p-value <0.001). Conclusion: Therapeutic group therapy can improve adolescents' self-development abilities (including growth and development tasks) and assertive behaviour. Therapy can be used as a learning program at school/home by involving teachers, parents, and the community to improve the quality of life for adolescents.